REVITALISASI KEARIFAN LOKAL TENTANG MATA AIR BAGI SISWA SMA KRISTEN WAIBAKUL, KABUPATEN SUMBA TENGAH, NUSA TENGGARA TIMUR - LASMAN, Diah Kartini (Bhakti: Jurnal Pengabdian Masyarakat, 2025)
Springs are a natural resource with significant ecological and cultural value for the people of Central Sumba Regency, particularly within the Marapu belief system. However, modernization and environmental changes threaten their sustainability. To revive local wisdom related to springs, the Community Service Team of FIB UI conducted a revitalization program at SMA Kristen Waibakul, Central Sumba. One of the main activities was an art competition themed "Springs in Sumbanese Culture," engaging students in interpreting the cultural and ecological values of springs through art. The competition received great enthusiasm, with 40 participants expressing their experiences and cultural identities through their artwork. The resulting artworks reflect a deep understanding of the role of springs in the lives of the indigenous Sumbanese people. Besides raising awareness of the importance of spring conservation, this activity also strengthened the younger generation’s pride in their local culture. The selected artworks were exhibited and published as an educational and promotional medium for local wisdom. This program is expected to serve as a model for sustainable, culture-based resource management.